(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Cloud computing is another technology regularly utilized virtualized with assets to give dynamically scalable assistance through the web. In the cloud computing, clients can access to the assets by utilizing a different gadgets, for example, workstations, PCs, advanced mobile phone, and so on to get to various assistance, for example, storage, projects, and application-improvement platforms, over help that gave by cloud suppliers through the web. This paper expects to give a safe, powerful, and adaptable technique to improve data storage security in cloud computing. Client with cloud computing can utilize the cloud services anyplace, all over, on-request and dependent on pay per use standard. Cloud computing has two sorts of models services models (SaaS, PaaS, and IaaS), and organization models (Public, Private, Community, and Hybrid cloud).